The influence of transformational leadership and accountability on organizational sustainability in United Arab Emirates: The moderating role of knowledge sharing - Faqera, Abdulaziz Fahmi Omar (2023)
Despite extensive research on enhancing sustainability performance of the public sector organizations in the country, there are still significant unanswered questions, and the sector has yet to fully realize its potential. Furthermore, the role of knowledge sharing as a moderator has not been previously examined. Therefore, this study aims to investigate the impact of transformational leadership and accountability on the sustainability of public sector organizations in the UAE. This research examines the moderating effect of knowledge sharing on the relationship between transformational leadership, accountability, and the sustainability of public sector organizations. The research framework integrates Social Exchange Theory (SET) and Resource-Based Theory (RBV). Data was collected from 531 employees working in public sector organizations in the UAE, specifically from four ministries. After screening the received questionnaires, 276 were deemed suitable for analysis. A stratified sampling technique was employed to ensure a representative sample. Quantitative analysis using Partial Least Squares structural equation modeling revealed a significant positive relationship between transformational leadership and economic and environmental sustainability. However, no support was found for the relationship between transformational leadership and social sustainability. Additionally, the results demonstrated a significant positive relationship between accountability and economic, environmental, and social sustainability. Moreover, knowledge sharing was found to moderate the relationship between transformational leadership and environmental sustainability, as well as accountability and economic, environmental, and social sustainability. However, the study did not find support for the relationship between transformational leadership and both economic and social sustainability. This study contributes to existing knowledge by providing a context-bound approach that refines and integrates social exchange theory and resource-based theory in the context of public sector organizations in the UAE. The findings have important theoretical, methodological, and practical implications, shedding light on the ways in which transformational leadership, accountability, and knowledge sharing can influence the sustainability of the country’s public sector organizations.